Conceptions of students with PIBID scholraship about the inclusive process in the towns of Araras and Alfenas - Fernanda Vilhena Mafra Bazon; Daniele Lozano; Claudia Gomes (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
This study looks for the analysis of the conceptions of graduation students, with scholarship of the Programa Institucional de Bolsas de Iniciação à Docência (Pibid), about the special education and of the inclusive education in the towns of Araras (SP) and Alfenas MG). Participated of this research 37 students of federal universities situated in the referred towns.  It was utilized a questionnaire with open and closed questions for the study.  The results aimed that 57.1% of the students of Araras and 60.9% of the students of Alfenas, have the knowledge about legislations that support the inclusive education.  In Araras:  76,9%, and in Alfenas:  60.9% of the students participated of events and courses abaout special education or school inclusion, but 76.9% (Araras) and 82.6% (Alfenas) considered themselves unprepared to act in classroom with students with special needs.  This fact may be supporting some present conceptions in the two towns, for example, 38.5% of the students of Araras and 39.1% of the students of Alfenas considered that there are not theirs responsibility to perform educational practices for those students in regular schools, attributing this fact to problems in their courses of graduation.  We emphasize that this study pointed to the need for critical discussion of scholar inclusion in initial training and the Pibid can be considered a privileged place for it.